PERAN MASYARAKAT DALAM MEMBENTUK LEARNING SOCIETY - Wathoni, Kharisul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
A discussion of the learning society has been issued by Torsten Husen in 1971. Learning society is the empowerment of communities and families in education. Within this time, the role of community and family in formal educational institutions has still lack of attention. Since the existence of school is in the midst of the society, certainly it should be an integral part of the surrounding community and it must not be moving around in the void of social life. Learning society is an effort to increase public participation in the management of learning resources provided in the community, hence this system may not be separated or remain an integral part of society as a whole. Through the efforts of this community empowerment, educational institutions plays an important role as the core of the learning society that can result in graduates who are qualified, capable, functional, and integrated with the community.Â ÙÙÙØ¯ ÙØ§Ù ØªÙØ±Ø³ØªÙÙ ÙÙØ³ÙÙ Ø¨Ø§ÙØªØ¹Ø±ÙÙ Ø¹Ù Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹ÙÙ Ø³ÙØ© 1971 Ù. ÙØ§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹ÙÙÙ ÙÙ ØªÙÙÙØ© Ø§ÙÙØ¬ØªÙØ¹ ÙØ§ÙØ£Ø³Ø±Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ©. Ø¥ÙÙ Ø§ÙØ¢ÙØ ÙÙ ÙÙÙ ÙÙØ§Ù Ø§ÙØªÙØ§Ù ÙØ§Ù Ø¨Ø¯ÙØ± Ø§ÙÙØ¬ØªÙØ¹ ÙØ§ÙØ£Ø³Ø±Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ±Ø³ÙÙØ© ( Ø§ÙÙØ¯Ø§Ø±Ø³). ÙÙÙÙ Ø§ÙÙØ¯Ø§Ø±Ø³ ÙÙ ÙØ³Ø· Ø§ÙÙØ¬ØªÙØ¹Ø ÙØ§Ø¨Ø¯ ÙÙ Ø£Ù ØªÙÙÙ Ø¬Ø²Ø¡Ø§ ÙØ§ ÙØªØ¬Ø²ÙØ¡ ÙÙ Ø§ÙÙØ¬ØªÙØ¹Ø ÙÙØ§ ØªØ®Ø±Ø¬ Ø¹Ù Ø§Ø·Ø§Ø± Ø§ÙØÙØ§Ø© Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ©.Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹ÙÙ ÙÙ Ø§ÙÙØØ§ÙÙØ© ÙØªØ±ÙÙØ© ÙØ´Ø§Ø±ÙØ© Ø§ÙÙØ¬ØªÙØ¹ ÙÙ Ø¥Ø¯Ø§Ø±Ø© ÙØµØ§Ø¯Ø± Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙÙØ¬ÙØ¯Ø© ÙÙ Ø§ÙÙØ¬ØªÙØ¹ ÙØ§Ø³ØªÙØ§Ø¯ØªÙØ§Ø ØØªÙ ÙØ§ ÙÙÙÙ ÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© ÙÙÙØµÙØ§ Ø£Ù ÙÙ Ø«Ø§Ø¨Øª ÙÙ ÙÙÙÙ Ø¬Ø²Ø¡Ø§ ÙØ§ ÙØªØ¬Ø²ÙØ¡ ÙÙ Ø§ÙÙØ¬ØªÙØ¹. Ø¨ÙØØ§ÙÙØ§Øª Ø§ÙØªÙÙÙØ© Ù Ø§ÙØªØ±ÙÙØ© ÙØ°ÙØ Ø£ØµØ¨ØØª Ø§ÙÙØ¤Ø³Ø³Ø§Øª Ø§ÙØªØ±Ø¨ÙÙØ© ÙØ±ÙØ²Ø§ ÙÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹ÙÙ ØØªÙ Ø®Ø±ÙØ¬Øª Ø§ÙØ®Ø±ÙÙØ¬ÙÙ Ø§ÙØ¬ÙÙØ¯ÙÙ Ù Ø°ÙÙ Ø§ÙÙÙØ§ÙØ§Øª Ø§ÙÙØ¸Ø§Ø¦ÙÙØ© Ø§ÙÙØªØØ¯ÙÙ Ø¨Ø§ÙÙØ¬ØªÙØ¹.Â Â Â